DESIGN OF DRINKING WATER DISTRIBUTION NETWORK SYSTEM AND DISTRICT METER AREA (DMA) AT MAJALAYA DISTRICT, BANDUNG REGENCY - Bahtiar Ramadani, Denis
Water distribution network is an essential infrastructure in urban water supply. Water distribution network planning technically have to consider the quantity, quality, and continuity aspect. This study aims to design a drinking water distribution network system properly at Majalaya District, Bandung Regency with its water loss management. In this study, secondary data and interviews was conducted from the local organization. The data processing was conducted using software ArcGIS Pro and EPANET 2.0. The design period is determined 10 years with total water demand 412 liter/second. Weighting was conducted using Simple Additive Weighting (SAW) method with comparison parameter including economic, technical, public health, environmental, and socio-economic. Based on weighting result, the chosen alternative for water distribution method is looping system based on land use with total pipe length of 28,367 m. The gravitation system is used with ground reservoir. District Meter Area (DMA) was designed to reduce non revenue water and divided the area study into 5 zones and 24 sub zone. Through this study, the number of Majalaya inhabitants served with adequate and safe drinking water is 70% by 2031 with the water loss less than 15%.